Seasonal flight activity and the length of the generation period of selected Noctuidae (Lepidoptera) –extent and causes of variation - Honěk Alois; Martinková Zdenka; Novák Ivo; Jauschová Terézia; Sarvašová Lenka; Saniga Miroslav; Holecová Milada; Kulfan Ján; Zach Peter (Folia Oecologica)
The variability in the timing of spells of flight activity was monitored in 25 monovoltine and 10 bivoltine species of Noctuidae (Lepidoptera) by evaluating their catches in a light trap operated nightly from April to November 1967–1995. We determined the day when 50% of the individuals of a particular generation were caught, T0.5. The intraspecific ranges of variability in T0.5 were 9 to 37 days, 29 to 41 days and 25 to 53 days in the monovoltine and the first and second generations of the bivoltine species, respectively. Annual changes in T0.5 were strongly correlated between species whose flight activity occurred during a similar period of the season. For bivoltine species, the abundance and T0.5 of the first and second generations were correlated. We calculated, for each species and generation, the length of the generation period (GP), i.e., the time from T0.5 of generation n to T0.5 of generation n+1. This quantity was then converted to the sum of degree-days above 10.7 °C (the thermal threshold for the development of Noctuidae) accumulated under natural conditions. The temporal sequences of these recalculated lengths of the GP were significantly correlated in 91% of the pairs of monovoltine species and in 98% of the pairs of first-generation bivoltine species. The correlations between the lengths of the GP confirmed that temperature determines the periodicity of flight activity, but this effect is modified by photoperiod.